Corps competency? III Marine Amphibious Force Headquarters in Vietnam - Morris, Michael F. 1963- (Modern war studies, 2024)
"The Vietnam War ended nearly fifty years ago, but it continues to engage, divide, and haunt the American public. The central paradox of the struggle endures: how did the world's strongest nation fail to secure the Republic of Vietnam's freedom? In Corps Competency?, Michael Morris addresses that vexing question by focusing on the senior Marine headquarters in the conflict's most dangerous region. The Vietnamese designated it I (or "Eye" in Marine parlance) Corps, a zone covering the northern five provinces of South Vietnam. This area featured the bloodiest fighting with the North Vietnamese Army, the Viet Cong's strongest infrastructure, the disputed border with North Vietnam, key portions of the Ho Chi Minh Trail, and the important political and economic prizes of Hue and Da Nang. This sector was also the site of the first major American military operation (Operation STARLITE), the battles of Hue City and Khe Sanh during the 1968 Tet Offensive, and a key military innovation known as the Combined Action Platoon (CAP), which was later cited as a counterinsurgency technique that could have won the war if applied more widely. Despite the region's importance, our understanding of the conflict in I Corps remains patchy. The contest there has been broken up into largely unconnected categories of analysis: the "grunt's eye" view, individual battles, specific units, debates over competing military strategies, and the influence of policymaking in Washington and Saigon. The result is that a half-century later, historians know comparatively little about the overall gestalt of the war in this pivotal locale. By approaching the regional conflict through the lens of the Third Marine Amphibious Force (III MAF)-the primary U.S. tactical command in I Corps from 1965-1970-Morris provides the first composite analysis of the critical role of the senior Marine headquarters and offers a coherence missing in piecemeal accounts of particular actions."